2010
DOI: 10.1590/s1984-46702010000100012
|View full text |Cite
|
Sign up to set email alerts
|

Species assemblages of zooplanktonic crustaceans in mountain shallow ponds of Chile (Parque Cañi)

Abstract: Even though the Chilean lakes are characterized by their oligotrophy, a transition from oligotrophy to mesotrophy, due human intervention, has been reported in some lakes. Nevertheless, there are still some pristine and unpolluted small lakes and ponds in mountain zones, free of human intervention and surrounded by native forests. Nine unpolluted, oligotrophic and pristine water bodies located in Cañi Park, a mountain zone with altitudes between 1000 to 1500 m a.s.l and forests where Nothofagus dombeyi, N. pum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…The literature indicates that Hyalella genus inhabits zones with high organic matter (Vainola et al, 2008), and this would agree with the direct association between H. costera and C. dubia obtained in the present study. These results would agree with similar observations for Andean ephemeral pools (De los Ríos and Roa, 2010) and southern Patagonian water bodies (De los Ríos-Escalante et al, 2010), where daphnid cladocerans can be found coexisting with species of the genus Hyalella. The presence of direct and indirect associations of some species with conductivity, total dissolved solids and pH would probably be due to the importance of calcium concentrations for crustaceans.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The literature indicates that Hyalella genus inhabits zones with high organic matter (Vainola et al, 2008), and this would agree with the direct association between H. costera and C. dubia obtained in the present study. These results would agree with similar observations for Andean ephemeral pools (De los Ríos and Roa, 2010) and southern Patagonian water bodies (De los Ríos-Escalante et al, 2010), where daphnid cladocerans can be found coexisting with species of the genus Hyalella. The presence of direct and indirect associations of some species with conductivity, total dissolved solids and pH would probably be due to the importance of calcium concentrations for crustaceans.…”
Section: Discussionsupporting
confidence: 92%
“…This zone is subject to human intervention due to forestry and agriculture (Figure 1). For this study it considered six and five groups for both groups of sites respectively (Figure 1), and considering their relatively close distance between lagoons and between groups of lagoons it would have homogeneity at species composition in both groups and it would have not risk of collect new species in lagoons of first group with six lagoons, in comparison to second group with five lagoons (Figure 1), similar situation has been reported for systems of close water bodies in Chilean Patagonia (Soto and De los Ríos, 2006;De los Ríos and Roa, 2010). In previous observations between 2009 and 2011 these groups of lagoons were present during early and middle southern spring (September to October; De los Ríos-Escalante et al, 2010); during late spring and summer they are dry, and the filling occurs during the rainy season in autumn and winter.…”
Section: Methodsmentioning
confidence: 56%
“…The presence of regulator factors or absence of random in zooplankton species assemblages in according to null model agrees with descriptions for Patagonian water bodies, where the marked environmental heterogeneity is the main cause of the presence of regulator factors in zooplankton assemblages (De los Ríos, 2008). An opposite situation occurs in sites with environmental homogeneity or with many species repeated in many of studied sites (De los Ríos et al, 2008b;De los Ríos and Roa, 2010).…”
Section: Discussionmentioning
confidence: 99%